English wood-engraving 1900-1950 - Balston, Thomas (Mineola, New York : Dover Publications, Inc., 2015)
"At the turn of the 20th century the art of wood-engraving enjoyed a flourishing revival among English artists. This volume showcases five decades' worth of magnificent black-and-white illustrations, with finely wrought images ranging from scenes of animals and rural life to episodes from literature. An informative history of the art is included"--
Includes bibliographical references (pages 20-21).
Keywords: Wood-engraving, English